2009
DOI: 10.1186/1471-2288-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous improvement in randomised clinical trials: meta-analysis of three-armed trials comparing no treatment, placebo and active intervention

Abstract: BackgroundIt can be challenging for patients and clinicians to properly interpret a change in the clinical condition after a treatment has been given. It is not known to which extent spontaneous improvement, effect of placebo and effect of active interventions contribute to the observed change from baseline, and we aimed at quantifying these contributions.MethodsSystematic review and meta-analysis, based on a Cochrane review of the effect of placebo interventions for all clinical conditions. We selected all tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
194
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(205 citation statements)
references
References 42 publications
5
194
3
3
Order By: Relevance
“…These reasons also explain why it is almost impossible to reliably judge in routine clinical practice whether a placebo effect has occurred. A recent analysis of trials including both a placebo and no-treatment control group also found relevant improvement in many no-treatment groups [29]. In conclusion, changes observed in patients receiving placebo over time are not a reliable way to estimate the size of placebo effects.…”
Section: What Is a Placebo Intervention In Clinical Practice?mentioning
confidence: 90%
“…These reasons also explain why it is almost impossible to reliably judge in routine clinical practice whether a placebo effect has occurred. A recent analysis of trials including both a placebo and no-treatment control group also found relevant improvement in many no-treatment groups [29]. In conclusion, changes observed in patients receiving placebo over time are not a reliable way to estimate the size of placebo effects.…”
Section: What Is a Placebo Intervention In Clinical Practice?mentioning
confidence: 90%
“…The contribution to the placebo response in RCTs of spontaneous symptom improvement was evaluated across different clinical conditions and was shown to be ~50% and it was >50% in nausea RCTs. 13 A number of meta-analyses and systematic reviews have discussed the size of the placebo response in RCTs in gastrointestinal disorders, such as IBD, functional bowel disorders (IBS, functional dyspepsia), gastric and duodenal ulcerations and GERD. These disease-oriented meta-analyses are listed in Table 1, together with major…”
Section: Placebo Responses In Clinical Trialsmentioning
confidence: 99%
“…The authors concluded that spontaneous variation and recovery of the symptoms provide a major contribution to the PR (and to the drug response) noted in clinical trials. In an attempt to differentiate between spontaneous remission and 'true' PR, the authors conducted a further metaanalysis of 37 three-arm trials that included both a placebo group and a 'no-treatment' control group [33]. They showed spontaneous healing to be high in symptoms such as nausea, depression, phobia, and pain; approximately 50% of the placebo effect seen was due to spontaneous remission.…”
Section: Placebo Response Rates In Experimental and Clinical Painmentioning
confidence: 99%
“…Although this seems rational in light of the reason the studies are usually conducted, to prove the clinical efficacy of a novel medication, they assume a simplified model of the PR that has recently been questioned: the additive versus nonadditive model of the PR [33]. In contrast, different methodologies are available to assess and quantify the PR itself and novel trial designs have been proposed to explore it further [34].…”
Section: Quantifying the Placebo Responsementioning
confidence: 99%